Students' Computational Thinking Ability on Learning of Integers - Ostian, Dyego; Hapizah, Hapizah; Mulyono, Budi (Tarbawi : Jurnal Ilmu Pendidikan, 2024)
Computational thinking is one of the most important skills in the 21st century; it is a thinking ability related to a set of mindsets that includes understanding problem-solving, reasoning at the level of abstraction, and developing problem-solving. This research is descriptive qualitative research that aims to determine the students' computational thinking ability and describe the computational thinking ability of 3 research subjects. The subjects of this study were 3 students selected from 28 students of class VII. The research instruments were test questions and interview guidelines. The results showed that out of 25 students, 14% were low-ability students, 75% were medium-ability students, and 11% were high-ability students. Students in class VII.1 were mostly able to fulfill the indicators of decomposition, pattern recognition, algorithmic thinking and abstraction, but only a few students who raised these indicators correctly